2022
DOI: 10.1186/s13073-022-01108-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals common epithelial response patterns in human acute kidney injury

Abstract: Background Acute kidney injury (AKI) occurs frequently in critically ill patients and is associated with adverse outcomes. Cellular mechanisms underlying AKI and kidney cell responses to injury remain incompletely understood. Methods We performed single-nuclei transcriptomics, bulk transcriptomics, molecular imaging studies, and conventional histology on kidney tissues from 8 individuals with severe AKI (stage 2 or 3 according to Kidney Disease: Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 77 publications
1
36
0
Order By: Relevance
“…( D-E ) snRNA-seq analysis of human kidney tissue from patients with severe AKI and controls (n=6-8). Analysis was performed on publicly available snRNA-seq data from Christian Hinze et al (39). ( D ) Bubble chart for top 10 enriched Hallmark pathways of upregulated DEGs in kidney ECs from patients with severe AKI compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…( D-E ) snRNA-seq analysis of human kidney tissue from patients with severe AKI and controls (n=6-8). Analysis was performed on publicly available snRNA-seq data from Christian Hinze et al (39). ( D ) Bubble chart for top 10 enriched Hallmark pathways of upregulated DEGs in kidney ECs from patients with severe AKI compared to controls.…”
Section: Resultsmentioning
confidence: 99%
“…This cell exhibited increased resistance to ferroptosis and proteotoxic stress driven by MYC-induced proliferative signaling ( Tourigny et al, 2022 ). SnRNA-seq results from patients with renal injury revealed that the distal convoluted tubules were enriched for novel damage-associated cellular states that drive renal injury through transcriptomic patterns related to oxidative stress, hypoxia, interferon response, and epithelial-mesenchymal transition ( Hinze et al, 2022 ).…”
Section: Specific Cell Types and Associated Signaling Pathways For Dkdmentioning
confidence: 99%
“…This manual annotation approach requires prior knowledge of canonical cell type markers in the given tissues and is often laborious and time-consuming. Although several automated cell type annotation methods have been developed [5][6][7][8][9][10][11][12][13] , manual cell type annotation using marker gene information remains widely used in scRNA-seq analysis [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] .…”
Section: Mainmentioning
confidence: 99%